The impact of music preferences, listening context, and social music engagement on emotional wellbeing among Malaysian youth - Mohamed Razali, Camellia Siti Maya; Ma’rof, Aini Azeqa (Human Resource Management Academic Research Society, 2024)
This study investigates the influence of music preferences, listening context (e.g., listening alone, with friends, or in social settings), and social music engagement (both active and passive) on emotional wellbeing among Malaysian youth aged 18-30. A quantitative approach was employed with a sample of 385 participants from various public and private institutions in Malaysia. Pearson correlation and multiple regression analyses were used to explore the relationships between the independent variables (music preferences, listening context, and social music engagement) and the dependent variable (emotional wellbeing). The findings revealed that active social music engagement was the strongest predictor of emotional wellbeing, followed by passive engagement and listening context. Music preferences also contributed significantly to emotional wellbeing, though its effect was relatively weaker. These results emphasize the importance of fostering both active and passive forms of music engagement and recognizing the contexts in which music is consumed to promote emotional wellbeing among youth. The study suggests that educational institutions and mental health practitioners should incorporate music-based strategies into wellbeing programs to enhance emotional health among youth.